2017
DOI: 10.3389/fneur.2017.00179
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Structural and Functional Networks and Their Correlation with Alertness in Right Temporal Lobe Epilepsy: A Graph Theory Study

Abstract: Previous studies have shown that temporal lobe epilepsy (TLE) involves abnormal structural or functional connectivity in specific brain areas. However, limited comprehensive studies have been conducted on TLE associated changes in the topological organization of structural and functional networks. Additionally, epilepsy is associated with impairment in alertness, a fundamental component of attention. In this study, structural networks were constructed using diffusion tensor imaging tractography, and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 52 publications
7
22
1
Order By: Relevance
“…MRI studies have revealed that brain functional connectivity, the amplitude of low‐frequency fluctuations (ALFFs), regional homogeneity (ReHo), the fractional anisotropy (FA) of white matter fibers, topological properties, and many other indicators are altered in patients with TLE (Bernhardt, Hong, Bernasconi, & Bernasconi, ; DeSalvo, Douw, Tanaka, Reinsberger, & Stufflebeam, ; Jiang, Li, Chen, Ye, & Zheng, ; Liao et al, ); thus, the function and structure of the brain in TLE patients are damaged to varying degrees. However, how the regularity and complexity of rs‐fMRI time series are altered in rTLE patients is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MRI studies have revealed that brain functional connectivity, the amplitude of low‐frequency fluctuations (ALFFs), regional homogeneity (ReHo), the fractional anisotropy (FA) of white matter fibers, topological properties, and many other indicators are altered in patients with TLE (Bernhardt, Hong, Bernasconi, & Bernasconi, ; DeSalvo, Douw, Tanaka, Reinsberger, & Stufflebeam, ; Jiang, Li, Chen, Ye, & Zheng, ; Liao et al, ); thus, the function and structure of the brain in TLE patients are damaged to varying degrees. However, how the regularity and complexity of rs‐fMRI time series are altered in rTLE patients is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 The small-world network is characterized by a high level of integration and segregation. [11][12][13][14][15] However, of these modalities, the DTI has been rarely used to investigate the connectivity in patients with focal epilepsy, [12][13][14][15] despite the reproducibility of graph theory metrics from structural connectomes based on DTI being remarkably accurate. [11][12][13][14][15] However, of these modalities, the DTI has been rarely used to investigate the connectivity in patients with focal epilepsy, [12][13][14][15] despite the reproducibility of graph theory metrics from structural connectomes based on DTI being remarkably accurate.…”
mentioning
confidence: 99%
“…17,18 In addition, they are highly modulated by attention, medications, and cognitive state. [12][13][14][15] Previous studies in patients with focal epilepsy using graph theory analysis have revealed various results, including both a more regular 4,20 and a more random network topology. Only a few studies investigated graph theoretical analysis in patients with focal epilepsy based on DTI, and most of them recruited patients with mesial temporal lobe epilepsy.…”
mentioning
confidence: 99%
See 2 more Smart Citations